IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATA PELAJARAN PAI DI SMA NEGERI 1 MOYO UTARA - Mawaddah, Ida Aulia; Parhun, Muhammad; Jayanti, Dewi; Susanti, Susanti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This research is based on the fact that Islamic Religious Education (PAI) still experiences a number of obstacles, especially related to conventional learning methods that are less interesting for students. This condition results in low motivation and student participation during learning activities, students tend to be passive, do not understand the material well, and have not been able to apply religious teachings in everyday life. The focus of this thesis is (1) how the Implementation of the Project Based Learning Model Improves Student Learning Outcomes in Islamic Religious Education Subjects for Class XI of SMA Negeri 1 Moyo Utara (2) to determine the Supporting and Inhibiting Factors for the Implementation of the Project Based Learning Model in Improving Student Learning Outcomes in Islamic Religious Education Subjects for Class XI of SMA Negeri 1 Moyo Utara. The research approach method used is a descriptive qualitative approach with data collection procedures using interview, observation and documentation techniques. The results of the study show that the Implementation of the PjBL Learning Model is able to provide a positive impact on student learning outcomes and encourage students to be more active in the learning process, and to be directly involved in every stage of learning, from planning to project implementation. This active involvement makes students understand learning more directly.